PENGARUH IKLAN MEDIA SOSIAL INSTAGRAM (INSTAGRAM ADVERTISEMENT) DAN ELECTRONIC WORD OF MOUTH (EWOM)TERHADAP MINAT BELI DI AYRIN MOMS & BABY CARE - Gst. Ayu Atun Luviana; Ejasa Sembiring; A.A.I.N Dyah Prami (Journal of Applied Management Studies, 2022)
This study aims to find out: (1) Instagram advertisement on buying interest at Ayrin Moms & Baby Care, (2) electronic word of mouth on buying interest at Ayrin Moms & Baby Care, (3) Instagram advertisement and electronic word of mouth on buying interest at Ayrin Moms & Baby Care. This research is a research of descriptive analysis using quantitative approach. Data collection using a questionnaire. The sample, in this study numbered 60 people and used probability sampling methods. Test validity using Alpha Cronbach. Data analysis uses multiple linear regressions. The results found that: (1) Instagram advertisement has a positive and significant effect on buying interest obtained Sig value. 0.016 < 0.05 identifies that H0 is rejected and H1 is accepted. (2) Electronic Word of Mouth has a positive and significant effect on buying interest obtained Sig.t value of 0.000 < 0.05 which identifies that H0 is rejected and H1 is accepted. (3) Instagram advertisement and electronic word of mouth jointly give a positive and significant influence on buying interest. The contribution orsimultaneous contribution of Instagram Advertisement variables and Electronic word of mouth to buying interest was 72.1% while 27.9% was determined by other variables that not researched in this study.